Higher rate of colon polyp detection aided by an artificial intelligent software - Iwatsuki, Masaaki; Harada, Kazuto; Baba, Hideo; Ajani, Jaffer A. (Translational Gastroenterology and Hepatology, 2018)
Colorectal cancer (CRC) is one of the most common malignancies in the United States and Europe (1,2). Detection and removal of colon polyps or early cancer is associated with a reduction in mortality from CRC (3). The adenoma detection rate (ADR) during screening colonoscopy is recommended as a measure of the quality of colonoscopic examination. Corley et al. reveled that a 1% increase in the ADR was associated with a 3% decrease in interval CRC incidence (4). More recently, a prospective study from Poland et al. showed 1% increase in the ADR was associated with a 6% reduced risk of interval CRC (5). However, the ADR varies widely, largely depending on the ability of gastroenterologist, time spent, and preparation quality. Unfortunately, adenoma miss rate remains high (6–27%) (6), despite of novel technologies, devises, and interpretation. It is partly because of well recognized blind spots on colonoscopies.